Pharmacometabolomics Reveals That Serotonin Is Implicated in Aspirin Response Variability. (16th July 2014) - Ellero‐Simatos, S; Lewis, JP; Georgiades, A; Yerges‐Armstrong, LM; Beitelshees, AL; Horenstein, RB; Dane, A; Harms, AC; Ramaker, R; Vreeken, RJ; Perry, CG; Zhu, H; et al.
Abstract : While aspirin is generally effective for prevention of cardiovascular disease, considerable variation in drug response exists, resulting in some individuals displaying high on‐treatment platelet reactivity. We used pharmacometabolomics to define pathways implicated in variation of response to treatment. We profiled serum samples from healthy subjects pre‐ and postaspirin (14 days, 81 mg/day) using mass spectrometry. We established a strong signature of aspirin exposure independent of response (15/34 metabolites changed). In our discovery ( N = 80) and replication ( N = 125) cohorts, higher serotonin levels pre‐ and postaspirin correlated with high, postaspirin, collagen‐induced platelet aggregation. In a third cohort, platelets from subjects with the highest levels of serotonin preaspirin retained higher reactivity after incubation with aspirin than platelets from subjects with the lowest serotonin levels preaspirin (72 ± 8 vs. 61 ± 11%, P = 0.02, N = 20). Finally, ex vivo, serotonin strongly increased platelet reactivity after platelet incubation with aspirin (+20%, P = 4.9 × 10 −4, N = 12). These results suggest that serotonin is implicated in aspirin response variability. CPT Pharmacometrics Syst. Pharmacol . (2014) 3, e125; doi:10.1038/psp.2014.22 ; published online 16 July 2014